Inherited metabolic disorders in adults: systematic review on patient characteristics and diagnostic yield of broad sequencing techniques (exome and genome sequencing) - Ferreira, Elise A.; Buijs, Mark J. N.; Wijngaard, Robin; Daams, Joost G.; Datema, Mareen R.; Engelen, Marc; Karnebeek, Clara D. M. van; Oud, Machteld M.; Vaz, Frédéric M.; Wamelink, Mirjam M. C.; Crabben, Saskia N. van der; Langeveld, Mirjam (Frontiers in Neurology, 2023)
The timely diagnosis of inherited metabolic disorders (IMD) is essential for initiating treatment, prognostication and genetic testing of relatives. Recognition of IMD in adults is difficult, because phenotypes are differerent from those in children and affected by acquired conditions. This systematic literature review aims to answer the following questions: 1) What is the diagnostic yield of exome/genome sequencing (ES/GS) for IMD in adults with unsolved phenotypes? 2) What characteristics do adult patients diagnosed with IMD through ES/GS have? A systematic search was conducted. Data from 695 articles, including 27,702 patients, were analyzed using different methods. The diagnostic yield for IMD in patients presenting with similar phenotypes was calculated. And the characteristics of patients diagnosed with IMD through ES/GS in adulthood were established. The diagnostic yield of ES and/or GS for adult patients presenting with unexplained neurological symptoms is 11% and for those presenting with dyslipidemia, diabetes, auditory and cardiovascular symptoms 10%, 9%, 8% and 7%, respectively. IMD patients diagnosed in adulthood (n=1426), most frequently portray neurological symptoms (65%), specifically extrapyramidal/cerebellar symptoms (57%), intellectual disability/dementia/psychiatric symptoms (41%), pyramidal tract symptoms/myelopathy (37%), peripheral neuropathy (18%), and epileptic seizures (16%). The second most frequently observed symptoms were ophthalmological (21%). In 47% of the IMD diagnosed patients, symptoms from multiple organ systems were reported. On average, adult patients are diagnosed 15 years after first presenting symptoms. Disease-related abnormalities in metabolites in plasma, urine or cerebral spinal fluid were identified in 40% of all patients whom underwent metabolic screening. In 52% the diagnosis led to identification of affected family members with the same IMD. ES and/or GS is likely to yield an IMD diagnosis in adult patients presenting with an unexplained neurological phenotype, as well as in patients with a phenotype involving multiple organ systems. If a gene panel does not yield a conclusive diagnosis, it is worthwhile to analyze all known disease genes. Further prospective research is needed to establish the best diagnostic approach (type and sequence of metabolic and genetic test) in adult patients presenting with a wide range of symptoms, suspected of having an IMD. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021295156, Registration number [CRD42021295156]